Digital lecturers in the making: Identity construction in Indonesia’s online English language teaching - Safriyani, Rizka; Retnaningdyah, Pratiwi; Munir, Ahmad; Malik, Zulfikri; Suhartono, Suhartono (Edelweiss Applied Science and Technology, 2025)
The change in Indonesia’s educational paradigm has substantially affected the training of aspiring lecturers teaching English as a second language. These lecturers must now instruct using a blended approach, incorporating online teaching sessions where they must produce their instructional strategies. This study examines how English Language Lecturers develop their identity while engaging in online teaching. This qualitative case study research offers a comprehensive examination of the development of professional identities among four lecturers based on interviews conducted with them. The data were gathered via semi-structured interviews and reflective writings. The interview questions were formulated according to Kelchtermans [1] framework of Lecturer Professional Identity. The data analysis utilized thematic analysis. The coding commenced with preliminary data analysis to discern repeating patterns and topics. The results indicate that the shift to online teaching has transformed these lecturers into ’digital lecturers.’ Their identities are affected by several elements, including task beliefs, personality traits, job motivation, self-image, and future aspirations. In addition, factors such as teaching experience, feedback, and competency in technology are crucial in shaping this process of identity formation. The study provides guidelines for improving the identity development of English Language Lecturers in digital educational contexts.